Applications of Google Trends as a Data Source for Statistical Models - Lenart, Klaudia (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
As technology advances, there is a growing number of potential data sources that can provide an alternative to traditional surveys. An example of this is the real time search popularity data made available through Google Trends. This type of data makes it possible to study public opinion, behaviour and attitudes in society or forecast economic phenomena. A definite advantage of using search popularity data is the immediate availability and low cost of obtaining such data. Also of significance is the fact that the Google Trends tool allows for direct research into the behaviour of Internet users, and not just their declarations as in the case of a survey. This can make a difference if respondents consider one of the answers to be more morally correct. Nevertheless, the use of Google Trends requires selecting correct search topics and terms to be included in the study and an awareness of the fact that the research sample is limited to Google search engine users. The paper will present the advantages and disadvantages of Google Trends and review its usefulness as a data source especially in times of higher market volatility.